Narrativas de convivencia en las relaciones de pareja de las mujeres gestantes y madres diagnosticadas con depresión del programa Gestar Futuro de la fundación Nutrir en la ciudad de Manizales (2022)
The objective of this research was to interpret the narratives of coexistence in the couple relationships of pregnant women and mothers diagnosed with Depression of the Gestar Futuro Program of the Nutrir Foundation in the municipality of Manizales, department of Caldas, Colombia.